Producción legislativa y representaciones políticas de la élite parlamentaria brasileña - Messenberg, Débora (2013)
This paper discusses the value contents of the legislative production and the discursive emissions of the Brazilian parliamentary elite between 1989 and 2006. The aims are to understand, from the résumés of the projects sent by members of the parliamentary elite of that term, and from their speeches about Brazilian politics and the political being of Brazil, in what ways different sociocultural nuances interfere with the construction and consolidation process of their careers and identities as politicians. The content analysis and the volume of initiative proposals by elite Parliament Members, as well as their discursive emissions about their performances as legislators, reveal that their respective regional ethos significantly model their practices and representations of Brazilian politics and of the political being in Brazil. These results reaffirm the perspective that political phenomena are charged with multiple uses and meanings, and in order to apprehend their complexity and relevance it requires interpretations that would also acknowledge for the importance of the field of values and of subjective assessment by social actors about their actions and political institutions. The analysis of Brazilian political life, from a sociocultural cutback, allowed for the construction of the original faction of the leading members of the Legislative Power, exposing a yet not much explored side of our political system.